TOWARDS BECOMING CRITICAL READERS AND WRITERS: ELT STUDENTS’ PERCEPTIONS ON THE EFFECTIVENESS OF CRITICAL READING AND WRITING INSTRUCTION - Bilki, Zeynep; Irgin, Pelin (International Online Journal of Education and Teaching, 2022)
Reading and writing underpinning all university study and beyond it are two essential skills that have significant influences on students’ growth in critical thinking. Students who aim to use English for academic purposes in higher education contexts need to develop their understanding of what it means to read and write critically in English with the support of critical thinking skills. While studies exist in understanding the nature and practice of critical thinking in academic writing or reading separately, studies that investigate the critical reading and writing (CRW) process from the perspectives of readers and writers are limited. The goal of this study was to explore how ELT pre-service teachers’ CRW skills changed from their perceptions of their own development depending on the critical reading and writing practices they experienced in the CRW course. The data was obtained from the participants' reflections collected before and after the instruction enriched with criticality. Thematic analysis revealed that our participants have had a clear sense of change in the way of their reading and writing in the process of becoming more critical readers and writers. The findings have implications for providing a pedagogical framework to foster CRW skills in higher education instructional settings.